(untitled) (Research, Society and Development, 2022)
Introduction: The delivery routes usually seen are cesarean delivery and normal delivery and, in Brazil, the cesarean rate shows an increasing trend, increasing from 38% to 57% between 2001 and 2014. Despite the contribution of this intervention to better health care, it is efficient that its indication is clinically justified, minimizing risks and adding benefits. Objective: to describe the historical behavior in the last 10 years of the type of delivery and its associated factors in Brazil and by regions according to data available in DATASUS. Results and discussion: From 2010 to 2020, a total number of 31887329 deliveries were recorded, represented by approximately 55% by the cesarean type. This amplitude was accentuated, observing a decline in the performance of vaginal delivery. Of the regions, only in the Northeast there was a predominance of the number of vaginal deliveries, in the period from 2010 to 2013, and in 2018, the number of cesarean sections exceeds, becoming similar to the other regions. It was found that there was no significant difference in the variation between the type of delivery and the year of delivery (p<0.08), but there was a significant correlation between gestational age, mother’s age and number of visits (p<0.008). Conclusion: there is prevalence of absolute and relative number of cesarean deliveries over vaginal deliveries, influenced by factors such as gestational age of delivery, mother’s age, purchasing and socioeconomic power, schooling, marital security, the number of prenatal consultations and prior access to information. Therefore, there is statistical analysis with significant difference that justifies the figures presented.